ENKAPSULASI LIGAN 4-(2-PYRIDYLAZO) RESORCINOL UNTUK RETENSI ION LOGAM CD(II) - Kusumawardhani, Hastari
Praconcentration technique for Cadmium (II) ion based on Flow Injection Analysis using 4- (2-pyridylazo) resorcinol (PAR) ligand has been done. Encapsulation of PAR ligand using 2% w/v Na-alginate solution and 0,1 M CaCl2 solution shown a spheric microcapsule. The microcapsule shows a reliable retention character for Cadmium (II) ion in pH 6. Static and dynamic retention capacity are 0,1 and 0,007 mg Cd(II)/gram microcapsule respectively. Utilization of PAR microcapsule as minicoloum for cadmium praconcentration and analysis based on Flow Injection Analysis (FIA) gives a good result. Bound Cd(II) ion was eluted using 1 mL HNO3 1 M. Analytical performance evaluation of this method showed a variance coefficient of 3,03% for 50 ?g/L standard solution. The calibration curve showed 0,9737 for linear equation on concentration range 10-100 ?g/L. Analysis result of concentration Cd(II) in various water sample are 3.38, 2.14, and 3.93 ?g/L for tap water, sea water, and Saguling water, respectively.